PENERAPAN MODEL PEMBELAJARAN GROUP INVESTIGATION-GUIDED INQUIRY UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA PADA MATERI KALOR KELAS XI SMA - Jessy Fitrianti; Azhar; Muhammad Sahal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted to address the low level of students’ science process skills in physics learning, particularly on the topic of heat. The limited involvement of students in scientific investigations and the predominance of conventional teaching methods have hindered the development of essential scientific skills. Therefore, this study aimed to determine the effect of the Group Investigation–Guided Inquiry (GI-GI) learning model on students’ science process skills. This research employed a quantitative approach using a quasi-experimental method with a posttest-only control group design. The population consisted of eleventh-grade students at SMA Negeri 5 Pekanbaru in the 2025/2026 academic year, with two classes selected as samples through normality and homogeneity testing. The experimental class was taught using the GI-GI learning model, while the control class received conventional instruction. Data were collected through a science process skills test consisting of 15 multiple-choice questions covering six indicators: observing, classifying, measuring, predicting, communicating, and concluding. The results showed that students taught using the GI-GI learning model achieved higher science process skills than those taught through conventional learning. The experimental class obtained an average score of 80.47%, while the control class achieved 76.09%, both categorized as good. These findings indicate that the implementation of the Group Investigation–Guided Inquiry learning model positively influences students’ science process skills by promoting active participation, collaboration, scientific communication, and critical thinking during physics learning. Therefore, the GI-GI learning model can be considered an effective alternative for improving students’ science process skills in learning heat concepts. Keywords: Group Investigation–Guided Inquiry, science process skills, physics learning, heat, quasi-experimental study.